Dietary and exercise intervention for patients with metabolic dysfunction associated steatotic liver disease (MASLD): a systematic review and meta-analysis. - Binika Gurung; Sujita Gurung; Nwe Ni (Sophia) Than (Clinical Medicine)
Introduction: A metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as non-alcoholic fatty liver disease (NAFLD), is one of the most common causes of chronic liver disease.1 MASLD currently affects around 30% of adults worldwide and is attributed to be the leading cause of liver transplantations.2,3 The risk factors for developing MASLD include being overweight or obese, insulin resistance, dyslipidaemia and hypertension.4 These risk factors can be managed through lifestyle interventions via dietary changes and exercise. Aims: This systematic review and meta-analysis study aimed to assess the impact of different types of diet and exercise on patients with MASLD. The primary outcomes of interest were body mass index (BMI), hepatic fat content (HFC) and liver stiffness (LS). The secondary outcome of interest was the change in liver enzymes and HbA1c. Methods: A systematic search for peer-reviewed randomised controlled trials (RCTs) was conducted on PubMed, MEDLINE, Scopus and Embase. Duplicates were removed and inclusion criteria were applied. The final studies were assessed for quality with the Cochrane Risk of Bias tool for RCTs. Data were then extracted, and STATA 18 was used for the meta-analysis. The DerSimonian and Laird random effects model was used. If meta-analysis was not possible, descriptive methods were utilised. Results: 40 RCTs were selected for review, with 18 focusing on diet, 11 on exercise and 11 on both. Dietary intervention had a positive impact on LS and HFC, but not on BMI. Exercise had a positive impact on BMI, LS and HFC, with aerobic exercise exerting the greatest effect on HFC.5–8 A combination of dietary changes and exercise did not appear to have a positive outcome on any of the parameters, which is most likely related to limited study data. Conclusion: The systematic review and meta-analysis show that dietary and exercise interventions can effectively improve liver fat and stiffness in patients with MASLD. 30–60 min of aerobic exercise 3–5 times a week provided the greatest effect, along with Mediterranean and low-calorie diets of at least 500 kcal reduction per day. Therefore, these lifestyle interventions would improve the burden that MASLD has on the NHS and the patient.